3-D simulation of local-scale traffic pollution. (20th February 2004) - Albergel, Armand; Jasmin, Florence
This paper presents some results of a 3-D study that ARIA Technologies carried out. The aim was to determine the effects of changes in road layout on the local air quality. 3-D software that solves the Navier-Stokes equations with a k - ε closure was used. The dispersion of the car exhaust emissions is computed for several meteorological profiles, and different car line positions on the road. At this scale, it is necessary to take into account the car movements, which can locally modify the flow, particularly in weak wind conditions. The effect was simulated by injecting turbulent kinetic energy, dissipation and momentum in the cells occupied by car lines. Moreover, these simulations show how the 2-D canyon effect is computed in a 3-D geometry, and how the introduction of the real geometry influences the result.